Experiences of the novice instructors of the Teaching Personal and Social Responsibility (TPSR) training program, model and transfer of learning - Havas, Elsa (2021)
Physical activity and Physical Education are seen as powerful tools to teach life skills for young people. Teaching Personal and Social Responsibility (TPSR) model promotes learning essential skills needed in life through physical activity. There is a need to develop and implement professional education programs to train experts on how to integrate life skills into physical activity and Physical Education. Novice physical activity instructors have been seen as a potential target group to learn and implement TPSR program. However, there is a lack of research on how instructors perceive training in the TPSR programs.